Acute gastroenteritis outbreak: epidemiology at the core of investigation. (30th September 2020) - Carvalho Sousa, S; Fernandes, S; Novais, L; Verne, M; Areias, R; Dourado, F; Ribeiro, M
Abstract: Background: At 28th February 2020, local public health authorities were notified that an occupational activity center headed to adult individuals with disabilities, in Guimarães (Portugal), had several cases of users vomiting or with diarrhea during that week, requesting control measures. Methods: An outbreak investigation was carried out, with case definition being someone with nausea, vomiting and/or diarrhea. An epidemic curve was made with the number of cases per date of symptoms onset. Attack rate was calculated as the number of cases in the occupational activity center divided by the number of people in the same center. Results: Mild, self-limited acute symptoms of nausea, vomiting and/or diarrhea were identified in 18 individuals that attended the occupational activity center. The first case developed symptoms on 24th February (day 0); the second case appeared about 24 hours after; the peak occurred at day 4 with seven cases. Attack rate was 27% among users and 15% among monitors. The mean age was 40 years. Two cases went to the emergency department and were clinically diagnosed with acute viral gastroenteritis, no further care needed. Meals were served at a neighbor building, shared with another rehabilitation institution. The rehabilitation institution reported zero cases. Additionally, Hazard Analysis and Critical Control Point process was fully accomplished. Conclusions: Clinical and epidemiological findings suggest a probable viral outbreak with person-to-person transmission. The incubation period is consistent with norovirus, the most common agent of viral gastroenteritis. No biological samples were collected, because symptoms were mild and there was no chance to do it. Environmental samples were not collected. Preventive hygiene measures were immediatly enhanced, namely hand washing, appropriate disinfection of contaminated surfaces and isolation if symptomatic. These measures are highly efficient breaking the chain of infection and that was obtained. Key messages: Epidemiological findings are at the core of an outbreak investigation and support immediate implemention of effective control measures. Although laboratory results are important, they are not always available for outbreak investigation.